Sanitation strategies & technologies : food-prone and high water table areas of Bangladesh - Kazi, Noor M.; ITN-Bangladesh (Network) (Dhaka : ITN-Bangladesh, Centre for Water Supply and Waste Management, BUET, 2003)
With reference to Dhaka, Patuakhali, and Sylhet districts of Bangladesh.
Includes bibliographical references (p. 81- 82).
Keywords: Sanitation -- Social aspects -- Bangladesh; Toilets -- Bangladesh